Nutritional Antioxidants and Lipid Profile in Newly Diagnosed Rheumatoid Arthritis Patients - BK, Manjunatha Goud; O, Sarsina Devi; N, Bhavna; RN, Devaki; K, Deepa; S, Niveditha (IIUM Medical Journal Malaysia, 2012)
Introduction: Rheumatoid arthritis (RA) is a chronic progressive autoimmune disorder characterized by symmetric erosive synovitis. The pathogenesis of bone erosion and joint deformities are not fully understood. The aim of this study was to find out vitamin C and E levels along with the lipid profile in newly diagnosed cases of RA. Materials and Methods: The patients for the study were selected from individuals attending the routine checkup in an Outpatient Department. Based on the criteria led by the American Rheumatism Association (ARA), the newly diagnosed patients were taken as cases and other normal individuals were taken as control group in the study. A total of 50 subjects were included in the study with the age group of 48 ± six years for both genders. Serum Vitamin-E was determined by the colorimetric method and serum Vitamin-C was estimated by the dinitro phenyl hydrazine method. Serum total cholesterol, HDL-cholesterol, triglycerides, and VLDL levels were estimated by the enzymatic method. LDL- cholesterol was calculated by the Friedewald's formula. Results: The levels of nutritional antioxidants vitamin E and C were different significantly in RA patients compared to control group. The lipid profile parameters were also different significantly in RA patients compared to the controls. Conclusion: Patients with RA presented with an imbalance in the oxidant-antioxidant system that markedly increased lipid peroxidation products and significantly decreased lipid soluble antioxidant vitamin E. These changes might play a role in the tissue damage and inflammation process in this disease.